Current State of Stroke Care in the Philippines - Collantes, ME. V.; Zuñiga, Y. H.; Granada, C. N.; Uezono, D. R.; De Castillo, L. C.; Enriquez, C. G.; Ignacio, K. D.; Ignacio, S. D.; Jamora, R. D. (Frontiers in Neurology, 2021)
Stroke remains the leading cause of disability and death in the Philippines. Evaluating the current state of stroke care, the needed resources, and the gaps in health policies and programs is crucial to decrease stroke-related mortality and morbidity effectively. This paper aims to characterize the Philippines’ stroke care network and care system using the World Health Organization health system building blocks framework. To integrate existing national laws and policies governing stroke and its risk factors dispersed across many general policies, the Philippine Department of Health (DOH) institutionalized a national policy framework for preventing and managing stroke. Despite policy reforms, government financing coverage remains limited. In terms of access to medicines, the government launched its stroke medicine access program (MAP) in 2016, providing more than 1,000 vials of recombinant tissue plasminogen activator (rTPA) or alteplase subsidized to selected government hospitals across the country. However, DOH discontinued the program due to the lack of neuroimaging machines and organized system of care to support the provision of the said medicine. Despite limited resources, stroke diagnostics and treatment facilities are more concentrated in urban settings, mostly in private hospitals, where out-of-pocket expenditures prevail. These barriers to access are also reflective of the current state of human resource on stroke where medical specialists (e.g., neurologists) serve in the few tertiary and training hospitals situated in urban settings. Meanwhile, there is no established unified national stroke registry thus, determining the local burden of stroke remains a challenge. The lack of centralization and fragmentation of the stroke cases reporting system leads to reliance on data from hospital records or community-based stroke surveys, which may inaccurately depict the country’s actual stroke incidence and prevalence. Based on these gaps, specific recommendations geared toward systems approach - governance, financing, information system, human resources for health, and medicines were identified.